Turner’s Syndrome (Archives of Pediatrics of Uruguay, 2022)
Introduction: Turner’s syndrome is a genetic disease characterized by total or partial loss of an X chromosome, its main features being low height, gonadal dysgenesis and characteristic phenotypic findings. It has a wide variability in its form of presentation.Large epidemiological studies show that morbidity increases in women with this syndrome, due to a wide range of associated diseases, especially cardiovascular disease, which significantly raises mortality.Objectives: to carry out a review of the literature, based on a clinical case in order to gather information regarding the latest treatment guidelines and present the new treatment goals.Conclusions: early diagnosis is essential, and has its own characteristics and suspicion criteria according to the stage in which it is carried out. The present challenge regarding the management of these patients consists of the training of a multidisciplinary medical team made up of a wide range of specialists able to carry out proper follow-up, in order to reduce complications and help the patient live a full life.We present a case of a patient with Turner’s syndrome assisted at the Pereira Rossell Hospital Center in Montevideo-Uruguay.
Keywords: Turner syndrome; Gonadal dysgenesis